Catalytic aerobic photooxidation of triarylphosphines using dibenzo-fused 1, 4-azaborines. Issue 32 (1st April 2022) - Kondo, Masaru; Agou, Tomohiro
Abstract : Dibenzo-fused 1, 4-azaborines (DBABs), which have received considerable attention in the field of organic electroluminescence devices, were successfully applied to the catalytic aerobic photooxidation of triarylphosphines in an aprotic solvent. Abstract : Although dibenzo-fused 1, 4-heteroaromatics are utilized as strongly reducing photocatalysts in organic synthesis and polymerization, they have rarely been employed in catalytic photooxidation. Moreover, to date, their boron-analogs, dibenzo-fused 1, 4-azaborines (DBABs), have not been applied in photocatalysis despite their promising potential as photocatalysts. Accordingly, herein, aerobic photooxidation of triarylphosphines (Ar3 P) was performed using DBABs as photocatalysts. The reaction smoothly proceeded in an aprotic solvent, and phosphine oxides were obtained in appropriate yields. Density functional theory calculations suggested that DBAB captured and activated phosphadioxirane intermediates, which were generated by the interaction of Ar3 P with 1 O2, at the Lewis acidic boron center.